Perancangan Learning Management System Menggunakan Object Oriented Design Pada STMIK Widya Cipta Dharma - Faslah, Ronny; Satria, Bagus; Benedictus Samponu, Yohakim (P3M Politeknik Negeri Banjarmasin, 2017)
As one of the best computer universities in East Kalimantan, STMIK Widya Cipta Dharma (STMIK WICIDA) always perform various development in teaching and learning process. One of the innovations that pioneered is the application of the concept of Blended Learning (integrated learning) is a learning process that combines the utilization of e-learning and conventional face-to-face learning. So the process of teaching and learning is not only happening in real class, but also in virtual classrooms where lecturers and students are physically separated. To support this, STMIK WICIDA seeks to build a Learning Management System (LMS) that can be accessed by students and lecturers. Students can access learning resources and online learning evaluations such as forum, quizzes, assignments, and teaching material. While lecturers can do classroom management, learning resources, and see the progress reports of student learning. This paper aims to provide Learning Management System design solution using object oriented design approach that can support the integrated learning process. The proposed system is an object-oriented design learning management model designed to support conventional face-to-face learning